Phytotherapeutic and ethnobotanical relevance of weed flora: A quantitative assessment from the cultivated fields of District Bajaur, Pakistan - Shah, Zubair; Shah, Ghulam Mujtaba; Gul, Alia; Ullah, Aziz; Haq, Aminul; Ullah, Irshad; Zeb, Mubarak; Rahim, Fazli (Ethnobotany Research and Applications, 2026)
Background: Agricultural weeds are widely used in traditional medicine due to their rich bioactive compounds that help treat a diverse range of diseases. This study was carried out to comprehensively document the ethnobotanical knowledge related to the weed flora associated with the agricultural landscapes of District Bajaur. This study provides the first systematic evaluation of the phytotherapeutic potential of weeds, offering a foundational baseline for subsequent pharmacological and ethnomedicinal research. Methods: Ethnobotanical data were gathered from local inhabitants through semi-structured questionnaires and interviews. Quantitative ethnobotanical indices, namely relative frequency of citation (RFC), use value (UV), and fidelity level (FL), were employed to assess the medicinal importance of each species and to elucidate their cultural and therapeutic relevance. Results: A total of 47 weed species belonging to 23 families were documented, with Poaceae being reported as the most dominant family (9 species). Among these, 36 species (77%) were dicotyledons and 11 species (23%) were monocotyledons, with annual weeds representing the majority (66%). Ethnobotanical information was obtained from 116 respondents (21 females and 95 males). The whole plant was the most commonly utilized part (70%). Silene conoidea L. exhibited the highest UV (0.89), while Plantago lanceolata recorded the lowest (0.51). The highest RFC was observed for Mentha longifolia (0.76), whereas Buglossoides arvensis showed the lowest (0.21). Similarly, Mentha longifolia demonstrated the highest FL (95.45%) used for the treatment of digestive disorders, dysentery, vomiting and abdominal pain, whereas Phalaris minor has the lowest FL (45.65%) used for cough and dysentery. Conclusions: The study confirms that local communities in Bajaur rely on medicinal weeds for primary healthcare needs. The comprehensive checklist of agriculture fields associated with weeds provides valuable baseline data for future research. Effective conservation measures are needed to preserve these important phytotherapeutic resources for sustainable use. Keywords: Ethnobotany; Ethnomedicinal Uses, Quantitative indices, Weed plants, Tib-e-Unani